National Cancer Institute’s Cancer Disparities Research Partnership Program: Experience and Lessons Learned - Wong, Rosemary S. L.; Vikram, Bhadrasain; Govern, Frank S.; Petereit, Daniel G.; Maguire, Patrick D.; Clarkson, Maggie R.; Heron, Dwight E.; Coleman, C. Norman (Frontiers in Oncology, 2014)
Purpose: To increase access of underserved/health disparities communities to National Cancer Institute (NCI) clinical trials, the Radiation Research Program (RRP) piloted a unique model - the Cancer Disparities Research Partnership (CDRP) program. CDRP targeted community hospitals with a limited past NCI funding history and provided funding to establish the infrastructure for their clinical research program. Methods: Initially, 5-year planning phase funding was awarded to six CDRP institutions through a cooperative agreement (U56). Five were subsequently eligible to compete for 5-year implementation phase (U54) funding and three received a second award. Additionally, the NCI Center to Reduce Cancer Health Disparities supported their U56 Patient Navigation programs. Results: Community-based hospitals with little or no clinical trials experience required at least a year to develop the infrastructure and establish community outreach/education and Patient Navigation programs before accrual to clinical trials could begin. Once established, CDRP sites increased their yearly patient accrual mainly to NCI-sponsored cooperative group trials (~60%) and Principal Investigator (PI)/mentor-initiated trials (~30%). The total number of patients accrued on all types of trials was 2,371, while 5,147 patients received navigation services. Conclusions: Despite a historical gap in participation in clinical cancer research, underserved communities are willing/eager to participate. Since a limited number of cooperative group trials address locally advanced diseases seen in health disparities populations, this shortcoming needs to be rectified. Sustainability for these programs remains a challenge. Addressing these gaps through research and public health mechanisms may have an important impact on their health, scientific progress and efforts to increase diversity in NCI clinical trials.